Technologie informacji i komunikacji w kształceniu przyszłych nauczycieli języka francuskiego. Wykorzystanie wirtualnych misji - Stańczyk, Joanna (My University, 2011)
Celem rozprawy jest opracowanie modelu kształcenia przyszłych nauczycieli języka francuskiego przygotowującego ich do ciągłego rozwoju zawodowego i osobistego. Ustanowiony profil zawodowy, określony jako „stawanie się ekspertem poprzez działanie eksperckie” (fr. expert en devenir), wskazuje cechę główną prowadzonych działań zawodowych i oznacza świadome korzystanie z wiedzy i umiejętności, umiejętność oceny własnych potrzeb kształceniowych poprzez analizę wyników podjętych działań, prowadzenie refleksji zawodowej już na etapie kształcenia. Do realizacji modelu opracowano przestrzeń dydaktyczną (fr. dispositif formatif) zawierającą odpowiednie zasoby (wirtualne misje, blogi, platformę edukacyjną) i stanowiącą środowisko umożliwiające prowadzenie wskazanych działań kształceniowych. Zakres rozważań wyznaczają poznawcza koncepcja konstruowania wiedzy uwzględniająca afektywny wymiar uczenia się oraz podejście socjokonstruktywistyczne. Sprawność i skuteczność kształceniowa modelu, opartego na refleksji i na interakcjach, została zweryfikowana poprzez obserwację, opis i wyjaśnienie podjętych działań kształceniowych i konstruowanych umiejętności. Ze względu na skoncentrowanie pracy na szczegółowej analizie procesów uczenia się/kształcenia (fr. apprentissage/formation), zastosowano metodologię „badanie w działaniu - kształcenie” (fr. recherche-action-formation) i wynikające z niej techniki zbierania danych: ankiety, wywiady, pisanie narracyjne, zapisy dyskusji.

The dissertation aims at constructing a pre-service teacher education model which assumes that prospective teachers of French receive training that prepares them for continuous professional as well as personal development. In the proposed professional profile, viewed as 'becoming an expert through performing expert-related activities' (French: expert en devenir), the student teacher's actions involve informed decisions concerning a practical application of his or her knowledge and skills, an independent evaluation of his or her own educational needs through analyzing the results of the previously undertaken actions, and professional reflectivity observable as early as in the process of the training itself. The model has been constructed around a specially designed pedagogical framework (French: dispositif formatif) containing appropriate teaching resources (enquiry-oriented lesson formats such as WebQuests, blogs, an educational platform) and providing a favourable environment for the pedagogical activities in question. The scope for the presently discussed issues is determined chiefly by the cognitive theory of knowledge construction wherein the affective dimension of the learning process and the socio-constructivist approach are given sufficient consideration. The effectiveness and efficiency of the model, based on reflectivity and interaction, has been verified through observation, description and explanation of the undertaken educational actions and thereby constructed knowledge and skills. Due to the fact that the main focus of the dissertation is a detailed analysis of the learning/ training processes (French: apprentissage/ formation) the applied methodology has centred around the 'action research – [teacher] training' paradigm (French: recherche-action-formation), thus the utilized research techniques of data collection: questionnaire, interview, narrative action evaluation report, discussion transcription.

L'élaboration d'un modèle de formation des futurs enseignants de français, susceptible de les préparer au développement professionnel et personnel continu, constitue l'objectif principal de l'étude. Le profil professionnel prôné, « expert en devenir », suppose dès la formation initiale un recours conscient au savoir et aux compétences, une capacité à évaluer ses propres besoins formatifs par l'analyse des effets des actions entreprises et une réflexion professionnelle qui deviennent ainsi la qualité principale des activités professionnelles entreprises. La réalisation du modèle élaboré s'est fait dans un dispositif formatif composé des ressources choisies (missions virtuelles, blogs, plate-forme éducative) et constituant un environnement propice à l'exécution des activités de formation. Le cadre théorique de l'étude est fondé sur la conception cognitive de la construction des connaissances avec sa dimension affective et sociale de l'approche socioconstructiviste. L'efficience et l'efficacité formatives du modèle, basé sur la réflexion et l'interaction, ont été vérifiées par l'observation, la description et l'explicitation des activités formatives menées et des connaissances en construction. Étant donné la focalisation de la recherche sur une analyse détaillée des processus de « l'apprentissage/formation », la méthodologie de la « recherche-action-formation », avec comme techniques de collecte de données : enquêtes, interviews, écriture narrative, discussions, a été mise en place.
Information and Communication Technologies in Training Prospective Teachers of French: Utilizing WebQuests
Technologies de l’information et de la communication dans la formation initiale des futurs enseignants de français. Exploitation des missions virtuelles
Wydział Neofilologii: Filologia Romańska
Keywords: Kształcenie nauczycieli; Teacher training; Formation initiale; Interakcje społeczne; Social interactions; Interactions sociales; Refleksja; Reflectivity; Réflexion; Rozwiązywanie problemów; Problem solving; Résolution de problèmes; TIK; ICT; TIC